Jejak Peradaban Islam di Era Budaya Digital: Transformasi dan Tantangan - Mawaddah, Arini Vina (Jurnal Peradaban, 2025)
This study aims to describe how the traces of Islamic civilization are changing within the development of digital culture and to identify the challenges that arise throughout this process. This research uses a descriptive qualitative method by collecting data through literature review and observing various forms of digital content that present Islamic values, history, and expressions. Data were analyzed using a thematic approach to identify patterns of transformation, such as the digitization of Islamic knowledge sources, shifts in the ways people learn about religion, and the emergence of more interactive modes of religious communication. The findings indicate that digital culture offers wide opportunities for preserving Islamic heritage through easier access to information, diverse learning media, and increased community engagement. However, the study also identifies significant challenges, including the spread of inaccurate religious information, a growing tendency toward superficial understanding, and the rise of religious content produced primarily for popularity. This research emphasizes the need for strong digital literacy so that the values and heritage of Islamic civilization remain preserved amid ongoing cultural change.